Atypical choroid plexus papilloma treated with single agent bevacizumab - Nasser, Selim M. (2014)
Choroid plexus papillomas (CPPs) are usually not malignant and occur in less than 1% of brain tumors in patients of all ages. They represent 3% of childhood intracranial neoplasms with a predilection in younger ages. Papillomas have an indolent course and carry a good long-term outcome if gross total surgical resection is achieved. However malignant evolution may occur, with a 10-30% incidence. Chemotherapy has been used with varied degrees of success. Most series are very small, some are only limited to case reports and cannot lead to guidelines or therapeutic recommendations. We are reporting the first case of recurrent CPP treated with 5 mg/kg of bevacizumab administered once every two weeks. Complete patient evaluations with follow-up contrast-enhanced magnetic resonance imaging (MRI) scans were obtained after the initial two treatments and every 8 weeks thereafter. Only after two treatments, the MRI scans showed radiological stabilization of the tumor, and the patient achieved an excellent clinical response with significant resolution of all skin lesions.